Risk Factor Examination and Education for Prevention of Diabetes Mellitus in Women in The Manado Sentrum Region: Risk Factor Examination and Education for Prevention of Diabetes Mellitus in Women in The Manado Sentrum Region - Wahongan, Greta Jane Pauline; Berhimpon, Siemona; Kapantouw, Nova Hellen (Sam Ratulangi University, 2025)
Diabetes Mellitus (DM) is a chronic disease which is reported to be the leading cause of death in Indonesia. The prevalence of DM increases along with increasing age and body weight, which are risk factors. The aim of this program is to examining risk factors and provide education for participants about preventing and controlling DM in Women in the Manado Sentrum Region. The method for carrying out this activity is to measure blood glucose index and found risk factors such as blood pressure and Body Mass Index. Activity participants were then given education regarding DM disease, risk factors, prevention and control of DM. The results of the activity showed that of the 36 participants, more than 50% were aged 55-74 years. Risk factors for DM such as being overweight and obese were experienced by 72.2% of participants, apart from that, hypertension was experienced by 41.7% of participants. Blood Glucose measurements showed that most were normal (72.2%), but 22.2% of participants were suspected of suffering from prediabetes and 2.8% was suspected of suffering from DM. Conclusion: More than half of participants have risk factors for DM, and are advised to adopt a healthy lifestyle in order to prevent or control DM.